2017
DOI: 10.1021/acs.energyfuels.7b02027
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid Alkoxysilane-Functionalized Urethane-Imide-Based Poly(ionic liquids) as a New Platform for Carbon Dioxide Capture

Abstract: Development of new and improvement of the existing materials for carbon dioxide (CO 2 ) capture is an urgent and significant goal for emission reduction. We hereby report synthesis of hybrid urethane-imide-based poly-ILs (HPILs) and their CO 2 capture capacities. The synthesized HPILs were characterized by Fourier transform infred (FTIR), nuclear magnetic resonance (NMR), differential scanning calorimetry (DSC), thermogravimetry analysis (TGA), dynamic mechanical thermal analysis (DMTA), atomic force microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 74 publications
1
20
0
1
Order By: Relevance
“…When the system reaches the desired temperature, the gas compartment is opened and CO 2 contacts the sample for the required time to achieve thermodynamic equilibrium. The amount of CO 2 adsorbed by the samples was calculated as described in literature (Bernard et al., 2017). Tests were carried out with pressure ranging from 0.06 to 1.5 MPa and temperatures of 25–45 °C.…”
Section: Methodsmentioning
confidence: 99%
“…When the system reaches the desired temperature, the gas compartment is opened and CO 2 contacts the sample for the required time to achieve thermodynamic equilibrium. The amount of CO 2 adsorbed by the samples was calculated as described in literature (Bernard et al., 2017). Tests were carried out with pressure ranging from 0.06 to 1.5 MPa and temperatures of 25–45 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Tests were performed in triplicate at 45°C of temperature and 0.4 MPa (equilibrium pressure). CO 2 solubility procedure, tests and calculation, was performed as presented in our previously published works 2,39 . Solid and liquid sorption kinetic was evaluated by controlling CO 2 sorption until saturation amount over time.…”
Section: Co 2 Sorption and Sorption Kinetics Assaysmentioning
confidence: 99%
“…Further research on their application in CO 2 /CH 4 separation demonstrated the possibility of PU-based PILs to overcome the CO 2 sorption capacity in comparison to linear PILs [ 121 ]. Furthermore, several hybrid urethane-imide PILs showed enhanced CO 2 sorption capacity in the CO 2 physisorption experiments [ 180 ]. Various attempts successfully yielded PILs incorporating polyepoxide building blocks [ 181 , 182 , 183 , 184 , 185 ].…”
Section: Polymeric Ionic Liquids (Pils)mentioning
confidence: 99%